Carl Nielsen, Saul and David and the Symbolist Movement: Cultural-Historical Perspectives - Zervides, Marie-Louise (Danish Yearbook of Musicology, 2017)
This article explores the position of the Danish composer Carl Nielsen (1865–1931) and his first opera Saul and David (1898–1901) in the European symbolist movement of the 1890s. Through a study of Nielsen’s published letters and diary entries from the period, it is possible to present the composer’s wide interest in art and engagement with artists – both in Denmark and on his extensive European travels – at a time when symbolism was dominating the modern art scene. Furthermore, one can trace artistic strategies in Nielsen’s early work – in this case, the opera Saul and David – that correspond to different ideas of symbolism. This includes combining archaic materials with contemporary techniques, as well as creating a subjective expression through mood and simplified, non-naturalistic styles.